An In Vitro Approach for Investigating the Safety of Lipotransfer after Breast-Conserving Therapy - Promny, Theresa; Kutz, Chiara-Sophia; Jost, Tina; Distel, Luitpold; Kadam, Sheetal; Schmid, Rafael; Arkudas, Andreas; Horch, Raymund E.; Kengelbach-Weigand, Annika (Journal of Personalized Medicine, 2022)
The application of lipotransfer after breast-conserving therapy (BCT) and irradiation in breast cancer patients is an already widespread procedure for reconstructing volume deficits of the diseased breast. Nevertheless, the safety of lipotransfer has still not been clarified yet due to contradictory data. The goal of this in vitro study was to further elucidate the potential effects of lipotransfer on the irradiated remaining breast tissue. The mammary epithelial cell line MCF-10A was co-cultured with the fibroblast cell line MRC-5 and irradiated with 2 and 5 Gy. Afterwards, cells were treated with conditioned medium (CM) from adipose-derived stem cells (ADSC), and the effects on the cellular functions of MCF-10A cells and on gene expression at the mRNA level in MCF-10A and MRC-5 cells were analyzed. Treatment with ADSC CM stimulated transmigration and invasion and decreased the surviving fraction of MCF-10A cells. Further, the expression of cytokines, extracellular, and mesenchymal markers was enhanced in mamary epithelial cells. Only an effect of ADSC CM on irradiated fibroblasts could be observed. The present data suggest epithelial–mesenchymal transition-like changes in the epithelial mammary breast cell line. Thus, the benefits of lipotransfer after BCT should be critically weighed against its possible risks for the affected patients.<br

The Impact of Irradiation and Lipotransfer on Healthy Mammary Cells after Breast-Conserving Surgery - Kutz, Chiara-Sophia; Jost, Tina; Distel, Luitpold; Kengelbach-Weigand, Annika; Hauck, Theresa; Horch, Raymund E. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16